ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL OPERASI HITUNG PECAHAN KELAS V SEKOLAH DASAR - Fitri Fitri; Hamdani Hamdani; Hery Kresnadi (Universitas Tanjungpura, 2020)
Abstract This study aims to find out the types of mistakes of students in solving fractional counting operations and their causal factors, and to describe them in grade V SDN 19 Sarilab.B Sambas County. The method in this research is descriptive method with the form of research, namely case study. The subjects in this study were sixteen students. Data collection techniques in this study are test and interview techniques. Based on the results of the research the mistakes made by students in completing fractional counting operations are conceptual errors, procedural errors and engineering errors. Conceptual errors include: 1) The summing error of the denominator is the same and not the same. 2) Denominator reduction errors are the same and not the same. 3) Multiplication errors and fractional division. 4) Error equalizing denominator using KPK and converting mixed fractions to ordinary fractions. Procedural errors include: 1) Errors in the addition and subtraction operations of fractions. 2) Error multiplication operation and fractional division. Engineering errors include: 1) Errors in counting summing up and reducing numerators. 2) Error in calculating multiplication. 3) Error counting when converting mixed fractions to ordinary fractions. Keywords : Analysis, Error Type, Causative Factors, and Fractional Counting Operation